Anthraquinone laxatives and human cancer: an association in one case. Issue 762 (April 1989) - Patel, P. M.; Selby, P. J.; Deacon, J.; Chilvers, C.; McElwain, T. J.
Abstract : An 18 year old girl presented with a leiomyosarcoma of the small bowel with widespread dissemination. Despite short term remissions after chemotherapy and surgery she died of the disease 10 months later. A history of prolonged exposure to danthron (an anthraquinone laxative) in childhood was obtained. Anthraquinones are known to be mutagenic and may be carcinogenic in experimental systems but danthron is not a proven carcinogen in man. The association of danthron and a rare bowel cancer in one case cannot prove a causative link. However, collection of further data seems advisable.